Calculation model of thermoelectric system for cooling discrete semiconductor devices - O. V. Evdulov; A. M. Ibragimova; T. Yu. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is to develop a computational model of a thermoelectric system (TPS) for cooling discrete semiconductor devices (DSD), implemented in the Elcut application software package, and to conduct a corresponding numerical experiment on it.Method. A new type of DPP cooling system has been developed, which uses several TEM sections that provide heat removal from both the lower and upper surfaces of the fuel elements, which increases the heat exchange surface between the cold source and the REE element and increases the heat removal efficiency. Using the finite element method, a computational model of this system is constructed based on the solution of the problem of thermal conductivity for a multi-element structure of a complex configuration, each component of which is characterized by thermal and electrical parameters.Result. A numerical experiment was carried out using the calculation model. As a result of it, the results of a numerical experiment were obtained in the form of a three-dimensional picture of the temperature field of the DPP - TPP system when it reaches the stationary mode, as well as graphs of temperature changes over time in the center of discrete semiconductor devices at various values of the cooling capacity of the thermoelectric module (TEM).Conclusion. As a result of the numerical experiment, it was found that the proposed design of the cooling TPP fully allows solving the problem of ensuring the required temperature regime of the DPP in the range of its power up to 75 W. At the same time, the use of sections of thermoelectric modules from thermoelements identical in their geometric, electrical and thermal characteristics makes it possible to increase the manufacturability of the device, as well as to ensure its operation in optimal current modes.